KINEMATICS OF A ROLLER CONE BIT WITH A DIRECT FACET TOOTH - Berezhnytskyi, B. S.; Vorobyov, M. S. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2018)
The advanced technique of shock-kinematic analysis of the bit roller cone interaction with rock in the process of oil and gas wells drilling is proposed. Preliminary investigations of the interaction of the roller cone bits with rock were based on assumptions far from reality: the concept of the instantaneous axis of rotation of the roller cone constant contact with rock, the absence of slipping, as well as the tooth reforming and sinking into rock. The principle of the roller cones action is the gradual destruction of the surface of the bottomhole due to the cutting-crushing chipping of rock with a bit tooth. The axial roller cone is considered, and the original method of planes projection is used to determine the regulation of tooth motion, taking into account: bit roller cones slipping along the surface of the bottomhole; phases of roller cone tooth sinking into rock; real change in the distance of the axis of rotation of the roller cone to the surface of the bottomhole due to tooth penetration into the rock; the substantiation of the conditions for avoiding the roller cone tooth entering to the previously obtained hole in the process of bottomhole crushing. Besides the moment of the drill string inertia, the moments of roller cones inertia are additionally taken into account under the condition of the oblique impact of the tooth on the rock. The technique allows to calculate the volume of the disintegrated rock on the bottomhole, both taking into account and without taking into account rock chipping and tooth forming. The obtained dependencies allow us to select transmitted ratios from the drill string to the crowns of the roller cones under the condition of avoiding the roller cone tooth to the previously obtained hole during rock destruction on the bottomhole. It allows increasing the efficiency of drilling by roller cones.